Legal Harmonization: Adultery in the Indonesian Criminal Code and Aceh Qanun No. 6/2014 on Jinayat Law - Anggi Siregar, Friska; Intan Meutia, Cut (State of Islamic Institute Langsa, 2023)
This paper discusses the complexity of the application of adultery laws in Indonesia, particularly in a comparison between the Criminal Code and the Aceh Qanun. The transformation of adultery regulations reflects the evolution of society's views and responses to social change. This research aims to understand the essence and implications of this regulatory transformation. In the context of legal harmonization, this research reveals the challenges and opportunities of harmonizing universal values with local and religious values, especially in the aspect of Islamic law in Aceh. The research conclusion provides a nuanced view of the dynamics of legal harmonization in Indonesia, emphasizing the need to create harmony in the legal system.